(untitled) (Malay Literature, 2017)
This article discusses Malay poems, especially as reflected in the syair of the Riau region, which have been classified as history poems. Two syair, Syair Kisah Engku Puteri and Syair Sultan Mahmud di Lingga, which each concern characters from the royal court of Riau-Engku Puteri Raja Hamidah and Sultan Mahmud Muzaffar Syah-will be focused upon. Tales about these two characters also appear in the historiographical text Tuhfat al-Nafis. On the whole, history poems are about events such as wars, travels, deaths, and marriages, and concern particular historical figures with the aim that these events are recorded. Using the concept of cultural memory to explore the relationship between history poems and memory, this article shows that the writers of both syair use their individual memories in their works. This is done in order to retain and store a private remembrance, and transforming it to produce a collective remembrance while shaping the public view of a fragment of history not captured in Tuhfat al-Nafis. Keywords: history poems, individual memory, collective memory, cultural memory